ELIMINATION OF OIL POLLUTION IN THE PRESENCE OF SURFACTANTS PRODUCED BY ACINETOBACTER CALCOACETICUS IMV B-7241, RHODOCOCCUS ERYTHROPOLIS IMV Ac-5017 AND NOCARDIA VACCINII IMV B-7405 - Pirog , T.P.; Sofilkanych , A.P.; Grytsenko , N.A. (Eurasian Journal of Applied Biotechnology, 2015)
Oil is currently the main source of energy used worldwide, which in turn increases the probability of this xenobiotic compound entering the environment. The physical and mechanical methods commonly used to eliminate oil spills are not always effective. Biological methods to eliminate oil pollution, based on direct introduction of oxidizing microorganisms (bioaugmentation) or the use of various compounds that stimulate the natural (autochthonous) microbiota (biostimulation), including microbial surface-active substances (surfactants) show much promise. Due to environmental safety, the ability to emulsify hydrophobic compounds, and improve the efficiency of microbial degradation of xenobiotics, surfactants can be widely used in environmental technologies. The article describes the use of surface-active substances (surfactants) produced by Acinetobacter calcoaceticus IMV B-7241, Rhodococcus erythropolis IMV Ac-5017, and Nocardia vaccinii IMV B-7405 to intensify the removal of oil from water and soil. It was shown that the degree of oil degradation in water (2.6-6.0 g/L) and soil (21.4 g/kg) in 30 days was 80-94% after treatment with the liquid microbial culture containing surfactants. It is assumed that the activation of the natural oil-oxidizing microbiota, primarily contributes to the degradation of oil present in water, in the presence of surfactants produced by A. calcoaceticus ІMV B-7241, R. erythropolis ІMV Ac-5017, and N. vaccinii ІMV B-7405.